Comparative analysis of the sensory acceptability of introduced Pro-Vitamin A-rich bananas in Eastern Africa - Nabuuma, Deborah; Ocimati, Walter; Simbare, Alice; Ekesa, Beatrice (International Society for Horticultural Science, 2022)
The wide banana diversity and reported high Pro-Vitamin A carotenoid levels in varieties originally outside Eastern Africa that are agronomically viable for the region indicates potential for banana in mitigating vitamin A deficiency. Materials and methods – This study analysed sensory evaluation results of Pro-Vitamin A-rich bananas (pVABs) and local varieties in Burundi, Democratic Republic of Congo (DRC), Tanzania, and Uganda using principle component analysis and factor analysis of mixed data to determine regional preferences and their implications on acceptability and promotion strategies in the region. Results and discussion – Acceptability varied with cooking method and site. pVABs acceptability was closer to that of local plantains and local plantains had a stronger association with South and North Kivu sites in DRC and Burundi compared to Tanzania and Uganda. Both local EAHB and plantains were highly acceptable and in contrast to each other. pVABs ‘Bira', ‘Apantu' and ‘Lahi' showed high potential acceptability across the four countries. Conclusion – Adoption of new varieties can potentially be hastened when their attributes are closely aligned to that of highly acceptable, predominant local varieties. Findings suggest a strong influence of socio-cultural settings including variety perception and preparation methods. Promotion of pVABs will benefit from country/site strategies that identify niche markets for each group and specific varieties along with the preferred cooking methods.